기술의 진보와 혁신, 그리고 사회변화: 특허빅데이터를 이용한 정량적 분석 - 김용대; Yongdai Kim; 정상조; Sang Jo Jong; 장원철; Woncheol Jang; 이종수; Jongsu Lee (Ŭngyong tʻonggye yŏnʼgu, 2016)
본 논문에서는 특허빅데이터를 분석하여 기술적 혁신과 사회변화의 관계를 규명하는 다양한 방법에 대하여 소개를 한다. 특히, 미국특허청에 1985년부터 2015년까지 등록된 4백만개 이상의 특허자료를 분석하였다. 먼저, 특허법의 변천사를 살펴보고 특허법의 발전이 특허활동에 미차는 영향에 대해서 살펴보았다. 두 번째로는, 국가별 기술군별 등록특허수를 바탕으로 군집분석을 이용하여 기술혁신 패턴이 비슷한 국가들로 군집을 만들고 각 군집의 기술혁신특징들을 살펴보았다. 세번째로는 특허간의 인용정보를 바탕으로 특허간의 네트워크를 구축하고 page-rank 알고리즘을 이용하여 주요특허를 탐지하는 방법을 설명하였다. 마지막으로, 정준상관분석을 이용하여 기술혁신과 사회변화와의 관계를 규명하였다. We introduce various methods to investigate the relations between innovation of technology and social changes by analyzing more than 4 millions of patents registered at United States Patent and Trademark Office(USPTO) from year 1985 to 2015. First, we review the history of patent law and its relation with the quantitative changes of registered patents. Second, we investigate the differences of technical innovations of several countries by use of cluster analysis based on the numbers of registered patents at several technical sectors. Third, we introduce the PageRank algorithm to define important nodes in network type data and apply the PageRank algorithm to find important technical sectors based on citation information between registered patents. Finally, we explain how to use the canonical correlation analysis to study relationship between technical innovation and social changes.